Evidence of the effect of dipyrone on the central nervous system as a determinant of delayed gastric emptying observed in rats after its administration - Collares,E.F. (2003)
Dipyrone administered intravenously (iv) delays gastric emptying (GE) in rats. The objectives of the present study were to assess: 1) the effect of the dose of dipyrone and time after its iv administration on GE in rats, 2) the effect of subdiaphragmatic vagotomy (VgX) and bilateral electrolytic lesion of the paraventricular nucleus (PVNX) on the delayed GE induced by the drug, and 3) the intracerebroventricular (icv) action of dipyrone and of one of its metabolites, 4-aminoantipyrine on GE. Male Wistar rats received saline labeled with phenol red intragastrically as a test meal. GE was indirectly assessed by the determination of percent gastric retention (GR) of the test meal 10 min after administration by gavage. Dipyrone delays GE in a dose- and time-dependent manner. Thirty minutes after the iv administration of 80 mg/kg dipyrone, the animals showed significantly higher GR (mean = 62.6%) compared to those receiving vehicle (31.5%). VgX and PVNX significantly reduced the iv effect of 80 mg/kg dipyrone (mean %GR: VgX = 28.3 vs Sham = 55.5 and PVNX = 34.5 vs Sham = 52.2). Icv administration of 4 µmol dipyrone caused a significant increase in GR (54.1%) of the test meal 10 min later, whereas administration of 4 µmol 4-aminoantipyrine had no effect (34.4%). Although the dipyrone dose administered icv was 16 times lower than that applied iv, for the same time of action (10 min), the GR of animals that received the drug icv (54.1%) or iv (54.5%) did not differ significantly. In conclusion, the present results suggest that the effect of dipyrone in delaying GE is due to the action of the drug on the central nervous system, with the participation of the PVN and of the vagus nerve.